2007
DOI: 10.1590/s1413-78522007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento das infecções pós artroplastia total de joelho: resultados com 2 anos de seguimento

Abstract: INTRODUÇÃO: A (ATJ) Artroplastia Total do Joelho é cirurgia de grande porte e sujeita a complicações pós operatórias, sendo a infecção uma das piores e mais temidas. No Instituto de Ortopedia e Traumatologia da Faculdade de Medicina da Universidade de São Paulo, a incidência de infecção nas ATJ tem se mantido ao redor de 3% nos últimos 3 anos. O objetivo desse estudo é analisar e padronizar o protocolo de tratamento das infecções pós artroplastia total de joelho. MATERIAIS AND MÉTODOS: Dentre os anos de 2003 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…Brazilian researchers 11 showed that females were preferentially affected among patients with TKA infection, with a prevalence of 65.51%, a result similar to the present study (69.23%). Furthermore, we found a significant associations of TKA infection with the age over 65 years (p = 0.023), unlike the results of Pinto et al, 19 which found no statistically significant association.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Brazilian researchers 11 showed that females were preferentially affected among patients with TKA infection, with a prevalence of 65.51%, a result similar to the present study (69.23%). Furthermore, we found a significant associations of TKA infection with the age over 65 years (p = 0.023), unlike the results of Pinto et al, 19 which found no statistically significant association.…”
Section: Discussionsupporting
confidence: 91%
“… 10 Some laboratory tests should be requested, such as erythrocyte sedimentation rate and the level of C-reactive protein (CRP) when infection is a suspicion. 11 Carvalho Junior et al 12 demonstrated the correlation of CRP and erythrocyte sedimentation rate levels, showing that these go back to normal levels 30-80 days after surgery. The correlation of physical examination, laboratory tests and imaging tests are essential for the diagnosis of prosthesis infection.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…33 We assume that these patients with infection could present immunosuppression (not investigated) as a consequence of poor alimentary conditions, inattention to personal care or systemic infectious diseases, inherent to the high age group, particularly in groups of socially unprotected elderly individuals. The obtainment of 74 (69%) excellent and 17 (15.9%) good results, indicates that the implants with the mobile tibial base will continue to be used; a long-term evaluation will evidence the persistence of such results, their advantages and disadvantages compared with those of the fixed tibial platform.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study that lasted a decade, Cruse and Foord (6) found 1.9% of infection in total hip prostheses, although the surgeries were performed in rooms without laminar flow and HEPA (high efficiency particulate air) filtration system. The incidence of infection in total hip arthroplasty in a specialized Brazilian university hospital was 13%, whereas in total knee arthroplasty, it has remained around 3% (7,9,10). Infections in orthopaedic surgeries can be severe and osteomyelitis is considered the most serious complication that can persist and lead to the functional deficiency of the extremities (8).…”
Section: Introductionmentioning
confidence: 99%